2014
DOI: 10.5937/socpreg1403383s
|View full text |Cite
|
Sign up to set email alerts
|

Educational and economic status of Roma in Serbia and its regional distribution

Abstract: Сажетак: У раду се проучава образовна и економска структура Рома у Србији. Истраживање се темељи на резултатима пописа, који су на територији Републике Србије спроведени 2002. и 2011. године. Уочене промене у образовној упоређују се са променама у економској структури Рома између два пописа. Сагледава се њихов узрок али и утицај на будући положај Рома у Србији. У раду се приказује и регионал-на расподела ове две значајне демографске структуре. Последњи део текста посве-ћен је анализи извора средстава за живот … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…More than 70% of the Roma are unemployed or have only temporary jobs (Radovanović & Knežević, 2014). Less than 50% finished primary school, and only 0.6% have a university degree (Sokolovska & Jarić, 2014). Finally, almost all of the studies have found that people hold extremely negative stereotypes of them (e.g., Mihić et al, 2016), and they are being discriminated against both institutionally and by individual members of the majority (Bašić, 2021).…”
Section: Research Contextsmentioning
confidence: 99%
“…More than 70% of the Roma are unemployed or have only temporary jobs (Radovanović & Knežević, 2014). Less than 50% finished primary school, and only 0.6% have a university degree (Sokolovska & Jarić, 2014). Finally, almost all of the studies have found that people hold extremely negative stereotypes of them (e.g., Mihić et al, 2016), and they are being discriminated against both institutionally and by individual members of the majority (Bašić, 2021).…”
Section: Research Contextsmentioning
confidence: 99%
“…The Roma, as a social group, are characterized by the cultural, social, religious, and residential diversity (Djordjević, 2010;Djordjević & Todorović, 1999;Škorić et al, 2014;Sokolovska, 2014), as well as social mimicry and a relative group closure that is not only reactive in type-a response to social isolation-but also a form of "protection of group identification and a way of preserving the group order and structure" (Sokolovska & Jarić, 2014). For several decades, the key characteristics of their social status have been (a) spatial segregation-a common practice of living in separate (ethnically cleansed) settlements that in appearance reflect the state of permanent misery of the majority of Roma population that is dramatically manifested in the organization and way of life; (b) an extremely unfavorable education structure and a high proportion of illiterate population in comparison to the same parameters of other ethnic groups in Serbia (Ministry for Human and Minority Rights of Serbia and Montenegro [MHMRSM], 2004); (c) frequent unemployment or engagement in least paid and stigmatizing positions; (d) a low level of inclusion in health and social care; (e) the lack of political participation, public action, and international organization (Mitrović, 1996;Todorović, 2011); and (f) low social capital-social relations of the Roma population in Serbia are primarily based on contacts, and the exchange of information and support within the immediate and extended kinship community, all of which makes social inclusion difficult.…”
Section: Cultural and Social Practices Of The Roma Community In Serbiamentioning
confidence: 99%